Synthesis and Antioxidant/Anti-Inflammatory Activity of 3-Arylphthalides - María J. Ortega; Belén Parra-Torrejón; Fátima Cano-Cano; Laura Gómez-Jaramillo; M. Carmen González-Montelongo; Eva Zubía (MDPI AG, 2022)
Phthalides are a group of compounds with relevant biological activities in different areas such as cytotoxicity, anti-stroke activity, neuroprotection, and inflammation, among others. In this study we designed and synthesized a series of 3-arylphthalide derivatives in order to identify their antioxidant and anti-inflammatory activities. The synthetic methodology was established in terms of atom and step economy through a dehydrative coupling reaction between 3-hydroxyphthalide and different properly functionalized arene rings. The evaluation of the antioxidant activity was performed by the ABTS assay and for the anti-inflammatory activity the inhibition of LPS-induced nitric oxide (NO) production in microglial cells Bv.2 and macrophage cells RAW 264.7 was measured. The synthesized compound 3-(2,4-dihydroxyphenyl)phthalide (5a) showed better antioxidant activity than the Trolox standard and caused strong inhibition of NO production in LPS-stimulated Bv.2 and RAW 264.7 cells. In addition, compound 5a reduced the expression of the pro-inflammatory cytokines Il1b and Il6 in RAW 264.7 cells. These results, which are the first account of the anti-inflammatory activity of 3-arylphthalides, suggest that compound 5a could be a promising candidate for more advanced anti-inflammatory studies.